Efficacy of neoadjuvant chemotherapy in patients with oral squamous cell carcinoma in a few selected centres in Klang Valley, Malaysia / Norul Mashirah Mohd Noor - Norul Mashirah, Mohd Noor (2019)
INTRODUCTION: Neoadjuvant chemotherapy (NAC) is purportedly advantageous in tumour reduction before definitive surgery is performed, with or without subsequent radiotherapy. Over the years, there have been conflicting results on the efficacy of NAC in advanced head and neck cancer, especially in oral cavity cancer. As the practice of NAC for oral squamous cell carcinoma (OSCC) is relatively new in Malaysia, there is a need to analyse the effectiveness of this treatment in the local settings for clinicians to consider NAC as a viable treatment option in future. This study aims to assess the effectiveness of NAC in patients with OSCC in Malaysia through histological assessment and podoplanin (PDPN) and VEGF expression. METHODOLOGY: For 14 OSCC patients treated with NAC, and subsequently surgery, tumour regression grading was performed using Tumour Regression Systems (Mandard-TRG, Ryan-TRG and AJCCTRG) on all surgically excised tumour specimen slides. The corresponding pre-treatment biopsy specimens were investigated for Podoplanin and VEGF expression through immunohistochemistry. RESULTS: Only 2 out of 14 cases showed complete tumour regression while 9 cases had mild to absence of regression. AJCC-TRG was significantly correlated with larger tumour size (ypT) (p=0.001) and strongly associated with advanced stage, positive margin, positive lymph node metastasis, extracapsular spread and poorly differentiated tumour. High expression of PDPN was observed in cases with mild to absence of tumour regression while VEGF expression demonstrated no correlation with tumour regression. CONCLUSION: NAC did not offer added benefit as a treatment option for OSCC. AJCC-TRG system is recommended in grading tumour response in NAC-treated head and neck cancer and OSCC. PDPN showed potential as prognosticator for OSCC and as predictor of poor tumour response to NAC. VEGF was neither a good predictor of tumour response to NAC nor a promising prognosticator for OSCC. iv Keywords: OSCC, Neoadjuvant chemotherapy, Tumour Regression Grading, Podoplanin, VEGF.